Empathy in family medicine trainees - Basílio, Nuno (2017)
Aim: The aim of this study was to assess empathy in family medicine trainees and to compare the level of empathy in first and final year trainees. Type of study: Cross-sectional. Location: Healthcare Regional Administrations (HRA) in Portugal. Population: Family medicine trainees in Portuguese HRA. Methods: We gave an anonymous, self-administered questionnaire, including the Jefferson Scale of Physician Empathy (JSPE), adapted and validated for Portugal, to a convenience sample of family medicine residents. The surveys were distributed in person or sent by personal e-mail. Statistical analysis was performed using SPSS (R) 19.0. Results: We collected 304 questionnaires. Of these, 84 were from trainees who began their training in 2012 (response rate (RR)=20.6%). The remaining 220 questionnaires were from trainees who began their training in 2016 (RR=42.3%). Most of the trainees were enrolled in programs in the Lisbon and Tejo Valley regions (52.4% and 61.4% respectively). There were no significant differences in gender between the two groups. There were no significant differences in the median levels (M) of empathy [ME(2012)=119.00; ME(2016)=118.00; p=0.678] between the first and final year trainees. Prior training in communication skills was not associated with a higher empathy score. Female participants had significantly higher empathy scores (p=0.008). Conclusions: Our results were comparable to national and international studies on empathy in medical students and trainees. Empathy does not seem to be associated with residency or undergraduate training. The low response rate obtained limits the representativeness of the sample and the validity of the findings. However this study presents an initial look at the variation in empathy during family medicine residency training in Portugal.